A delayed diagnosis of eosinophilic granulomatosis with polyangiitis complicated with extensive artery occlusion of lower extremities in children: case report and literature review - Xiaoliang Liu; Lin Wang; Kaiyu Zhou; Yimin Hua; Xiaoqing Shi; Chuan Wang (BMC, 2019)
Abstract Background Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare systemic vasculitis in children. A delayed or missed diagnosis of pediatric EGPA is common, owing to the atypical clinical manifestation and limited recognition of this disorder. The vasculitis in EGPA typically involves small to medium size vessels. Extensive occlusion of arteries in the extremities was being extremely rare and has never been reported in children. Case presentation A 10-year and 10-month-old girl with recurrent wheezing and breathlessness during exercise, was initially diagnosed with asthma at the age of five years. Despite unexplained manifestations, including intermittent remarkably increased eosinophilia, uncontrolled allergic rhinitis, and recurrent petechia, from the onset of asthma through to its remission, the consideration of EGPA was completely ignored until the patient presented with aggravated petechia and severe ulceration of the lower extremities, associated with extensive stenosis and/or occlusion of the arteries of the shank and foot. Given her history of asthma, eosinophilia, allergic rhinitis, mononeuropathy, pulmonary infiltrates, and vasculitis confirmed by the skin biopsy, the diagnosis of EGPA was ultimately confirmed. Regrettably, the initial inappropriate and irrational use of corticosteroid failed to relieve the symptoms until more aggressive treatment with intravenous methylprednisolone was started. This was followed by methotrexate treatment, with tapering of prednisone, without relapse over a six-month follow-up. Conclusions Pediatric rheumatologists should be alert to the possibility of EGPA in children with refractory asthma associated with unexplained manifestations, and should be aware of the thromboembolic complications as vascular sequelae of EGPA.